2019
DOI: 10.1038/s41598-019-43043-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis to assess the relationship between human and bovine brucellosis in South Korea, 2005–2010

Abstract: The first case of human brucellosis in South Korea was reported in 2002, and cases of human infection continue to occur. Although an association between human and bovine brucellosis has been identified, the spatial relationship has not been studied in South Korea. Here, we analysed the spatial patterns of human and bovine brucellosis retrieved from the human and veterinary surveillance data, as well as the spatial correlation between human and bovine brucellosis and associated factors that contribute to its oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…Brucellosis is prevalent in Italy, Germany, Turkey, Iran, Kazakhstan, China, and other countries, along with the Silk Road. Moreover, a considerable number of Brucella strains characteristic of pathogenic bacteria population and Brucella biovars was similar to the previous study; B. melitensis is the most important zoonotic agent, followed by B. abortus and B. suis (35,36). This correlates with the fact that the worldwide control of bovine brucellosis (due to B. abortus) has been achieved to a greater extent than the control of sheep and goat brucellosis (due to B. melitensis), these latter species being the most important domestic animals in many developing countries (17).…”
Section: Discussionsupporting
confidence: 88%
“…Brucellosis is prevalent in Italy, Germany, Turkey, Iran, Kazakhstan, China, and other countries, along with the Silk Road. Moreover, a considerable number of Brucella strains characteristic of pathogenic bacteria population and Brucella biovars was similar to the previous study; B. melitensis is the most important zoonotic agent, followed by B. abortus and B. suis (35,36). This correlates with the fact that the worldwide control of bovine brucellosis (due to B. abortus) has been achieved to a greater extent than the control of sheep and goat brucellosis (due to B. melitensis), these latter species being the most important domestic animals in many developing countries (17).…”
Section: Discussionsupporting
confidence: 88%
“…13 A previous study in Jordan in children , 15 years of age reported high seropositivity in Ma'an and Mafraq (the northern Badia) governorates. 11 Regional differences of human brucellosis within the same country were also reported in the Republic of Georgia, 14,15 South Korea, 16 and China. 17 Ownership of cows and camels was not associated with Brucella seropositivity in the multiple logistic regression model, but ownership of small ruminants (sheep and/or goats) was associated with seropositivity.…”
Section: Discussionmentioning
confidence: 74%
“…The hotspots of human brucellosis were clustered in the southeast regions of Korea. The risk of human brucellosis increases in rural regions, with the highest risk from bovine brucellosis [ 9 ]. The first case of human brucellosis caused by B. melitensis [ 10 ] and a foodborne outbreak of human brucellosis (n = 5) in South Korea was reported between 2012 and 2013 [ 11 ].…”
Section: Asiamentioning
confidence: 99%